Exploring Co2-Laser Microperforation: Potential for Enhanced Mass and Thermal Diffusion in Banana (Musa Sapientum) Dehydration - Gimenez-Castillo, B (SPRINGER, 2025)
This study investigates the potential application of CO2-laser microperforation as a pre-treatment to reduce energy consumption and drying time using three approximate pore density (6, 11 and 24 pores <middle dot> cm(-2)) and two pore size (220.89 +/- 14.15 and 431.96 +/- 19.92 mu m) to enhance water removal from banana slices during air-drying at 60 degrees C and 1.2 m <middle dot> s(-1). The results demonstrate that CO2-laser microperforation significantly reduced the dehydration time by up to 40% (from 169 min in control samples to 102 min in treated samples) due to an increased rate of water diffusion. This enhancement was corroborated by a 1.7-fold increase in the effective diffusivity coefficient, a 2.17-fold increase in the surface area-to-volume ratio, and a 1.11-fold improvement in energy absorption tendencies. Post-dehydration analyses revealed that the mechanical and color properties of the banana slices were strongly influenced by the CO2-laser operational settings, with optimized properties observed for subsequent processing steps. These findings suggest that integrating CO2-laser microperforation with air-drying processes offers a promising approach to reducing drying times and energy consumption in the food industry, providing a significant advancement in food dehydration technologies.
Keywords: Air drying; Mass diffusion; CO2-laser microperforation; Micro-estructural modification